COULOMB DRAG RESISTIVITY IN DOUBLE-LAYER GRAPHENE: INHOMOGENEITY EFFECTS - Manh Tien Nguyen; Van Men Nguyen (Tạp chí Khoa học Đại học Đà Lạt)
We investigate Coulomb drag resistivity in a double-layer system consisting of two parallel monolayer graphene sheets. In calculations, we employ the random-phase approximation to determine the polarizability functions of the graphene layers and the frequency-dependent dielectric function of the structure, taking into account inhomogeneity effects of the background dielectric. Our numerical calculations reveal that Coulomb drag resistivity in double-layer graphene systems steadily increases with increasing temperature but quickly decreases as the interlayer separation increases. The drag resistivity between the two layers in the case of an inhomogeneous background dielectric is substantially larger than that in the case of a homogeneous one. In addition, both the value and the imbalance in carrier density in the layers lead to noticeable changes in Coulomb drag resistivity in the system. Our study results are useful in graphene-based structure applications.